Fixation of potassium in Finnish soils - Kaila, Armi (Agricultural and Food Science, 1965)
The fixation of potassium in Finnish soils was studied on the basis of a material consisting of 265 samples from various parts of the country. A »wet method» was employed in which 2.5 me K was added per 100 g soil, and the fixation against the extraction with neutral N ammonium acetate was determined after a period of contact of one hour. The average fixation in the 135 samples of surface soils was 0.38 ± 0.03 me K/100 g soil, and in the 130 subsoil samples 0.77 ± 0.09 me/100 g soil, or about 15 and 30 per cent of the added potassium, respectively. In the groups of the surface samples the mean values increased with the increasing content of clay from 0.25 ± 0.04 me K/100 g soil in the finesand soils to 0.56 ± 0.03 me K/100 g soil in the samples of heavy clay containing at least 60 per cent of the fraction < 2 μ. In the groups of the subsoil samples the corresponding mean values were 0.33 ± 0.24 and 1.04 ± 0.15 me K/100 g soil. In the surface soils the results ranged from 0.09 me K/100 g in a finesand soil to 1.27 me K/100 g in a clay loam, and in the subsoil samples from 0 in a sandy clay soil to 1.80 me K/100 g in one sample of clay loam and one sample of silty clay. The fixation was positively correlated with the contents of finer clay <0.6 μ (r = 0.52***), coarser clay, 0.6–2 μ (r = 0.38***), pH (r = 0.36***) and negatively correlated with the content of organic carbon (r = —0.41***). These four variables explained 46 per cent of the variation in the fixation of potassium. Statistical analyses performed on the various groups showed that pH appeared to be particularly important in the group of finesand, silt and loam soils, while the content of organic carbon seemed to be noteworthy both in the clay soils and in the soils of the coarser texture. Further studies are needed to show whether the fairly high fixation in some soils of a coarser texture may be partly attributed to the fractions of silt. The factors influencing the fixation of potassium are discussed.